Adenet le Roi's Berte aus grans piés : Edited with Introduction, Variants, and Glossary - Adenet, le Roi, active 13th century (Studies in the Romance languages and literature, 2019)
The complete text is followed by a listing of proper names and a table of variants based on six other versions of the manuscript. The introduction gives the background of the author, the work, and the legend and discusses the seven versions and language used.